2018
DOI: 10.3126/nmcj.v20i4.25128
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Tricuspid and the Mitral Valve in Adult Human Heart: A Cadaveric Study

Abstract: The human heart valve is an integral structure and the valvular heart disease is one of the most common disease of the heart. Such cardiac disease require repair of the valve and valve replacement surgery where the patient’s diseased valve is replaced by a prosthetic valve. The aim of this study was to measure the annular circumferences and diameters of tricuspid and mitral valves in cadavers. A morphometric study was conducted in Department of Anatomy at Nepal Medical College and Teaching Hospital where total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…However, the data in the previous studies showed some different results compared with this study. Before formalin fixation, the average heart valve circumference in this study was slightly higher than in almost all the previous studies [5][6][7][8][9][10][11][12][13][14] , but lower than that reported by Tei et al 15 and coincided with those reported by Jatene et al 8 and Alison et al 23 Nevertheless, the average heart valve circumference after formalin fixation was slightly lower or similar to the above-mentioned studies. Why there was such a difference between our study and previous studies might be explained by the different socio-economic status and population groups from which the hearts were obtained as well as by the factors affecting formalin fixation, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, the data in the previous studies showed some different results compared with this study. Before formalin fixation, the average heart valve circumference in this study was slightly higher than in almost all the previous studies [5][6][7][8][9][10][11][12][13][14] , but lower than that reported by Tei et al 15 and coincided with those reported by Jatene et al 8 and Alison et al 23 Nevertheless, the average heart valve circumference after formalin fixation was slightly lower or similar to the above-mentioned studies. Why there was such a difference between our study and previous studies might be explained by the different socio-economic status and population groups from which the hearts were obtained as well as by the factors affecting formalin fixation, as mentioned above.…”
Section: Discussionsupporting
confidence: 87%
“…16 Many studies have been carried out in formalinfixed hearts rather than fresh human hearts. 6,[9][10][11]13,15 Formalin is widely used to preserve tissues for routine histological examination. The most common formula is 10% formalin, consisting of 3.7% formaldehyde in water with 1% methanol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations